Towards Optimal Business Regulatory Governance in India Report of the Working Group on Business Regulatory Framework - Planning Commission (Planning Commission, 2011)
This Report deals with the proceedings and findings of the Working Group on Business Regulatory Framework (WG BRF) - a cross-cutting Working Group that was constituted under the Steering Committee on Industry by the Planning Commission of India. The mandate of the WG BRF was to inquire into the current status of business regulatory regime in the country and to suggest actions thereof for enhancing business performance in general and manufacturing sector competitiveness in particular. The inputs of the WG BRF, along with those of the other Working Groups, will be utilised towards the formulation of the National Manufacturing Plan (NMP) as well as the Twelfth Five Year Plan (XII FYP) for the country.
Planning Commission Government of India
Planning Commission Government of India